Zambia's school re-entry policy for adolescent mothers: Examining impacts beyond re-enrollment. (January 2019) - Zuilkowski, Stephanie Simmons; Henning, Margaret; Zulu, Joseph; Matafwali, Beatrice
Highlights: Implementation of Zambia's school re-entry policy is uneven. The policy aims to support girls' enrollment, but does not function as intended. Pregnant girls with policy awareness were less likely to be forced from school. Young mothers with policy awareness perceived less stigma in the communities. Abstract: The persistently high rate of adolescent pregnancy, particularly among poor girls and in rural areas, is one of the reasons that universal secondary school completion remains elusive in Zambia. We used a mixed methods approach to explore how Zambia's re-entry policy is related to young mothers' outcomes beyond re-enrollment in school. We found that girls with knowledge of the policy were less likely to be forced out of school while pregnant and perceived less stigma after delivery. The policy also had the potential to enlist support for girls' continuation in school, though its implementation often fell short of its potential.